2019
DOI: 10.1039/c8ra08163h
|View full text |Cite
|
Sign up to set email alerts
|

A targeted biocompatible organic nanoprobe for photoacoustic and near-infrared-II fluorescence imaging in living mice

Abstract: We developed a targeted organic nanoprobe for both photoacoustic imaging and near-infrared-II fluorescence imaging in living mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The IR1061 dye a commercial dye with high NIR-II (1064 nm) absorbance and low fluorescence quantum yield, and holds promise as a NIR-II photothermal agent but the hydrophobicity of IR1061 limits its use in biomedical applications. [31][32][33] In order to overcome this limitation, further modifications of the IR1061 are required.…”
Section: Introductionmentioning
confidence: 99%
“…The IR1061 dye a commercial dye with high NIR-II (1064 nm) absorbance and low fluorescence quantum yield, and holds promise as a NIR-II photothermal agent but the hydrophobicity of IR1061 limits its use in biomedical applications. [31][32][33] In order to overcome this limitation, further modifications of the IR1061 are required.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the superiorities mentioned earlier, the development of organic molecular dyes is restricted by their susceptibility to photobleaching and diffusion and their water-immiscibility. To address these limitations, Xie and colleagues developed a targeted biocompatible organic nanoplatform [IR-PEG-folic acid (FA)] through self-assembly of elemental components in the phosphatebuffered saline (PBS) [58]. The IR-PEG-FA nanoplatform, composed of a hydrophobic organic dye IR-1061 and a hydrophilic PEG chain with an FA-targeting group (Figure 4F), exhibited excellent stability, strong NIR absorption and NIR-II emission, low cytotoxicity, and high metabolic activity, showing significantly enhanced signal contrast and brightness in PAI and NIR-II fluorescence imaging.…”
Section: Trends Trends In In Chemistry Chemistrymentioning
confidence: 99%
“…More sophisticatedly, Xie et al demonstrated a multi-modal contrast agent after the judicious chemical modification of IR-1061 dye [101]. As depicted in Figure 19, the agent not only exhibited NIR-II imaging properties due to the commercial NIR dye (pink), but also was biocompatible due to the PEG moiety (blue) and was functionalized with a cancer-targeting folic acid moiety (orange).…”
Section: Organic Semiconducting Materials For Near-infrared Imagingmentioning
confidence: 99%